Aquaporin membrane channels in oxidative stress, cell signaling, and aging: recent advances and research trends - Tamma, Grazia (2018)
Fil: Fil: Tamma, Grazia. University of Bari “Aldo Moro”. Department of Biosciences, Biotechnologies and Biopharmaceutics; Italy.